Surging São Tomé: Waiting for Oil in the Gulf of Guinea - Seibert, Gerhard (2014)
A two-island nation in the Gulf of Guinea, São Tomé and Príncipe is Africa's second-smallest country, with population of 187,000. It is a peaceful Creole society without ethnic, religious, or linguistic cleavages. Yet and Príncipe is an impoverished country -- as of 2011, it possessed the world's third smallest national economy, its GDP per capita was just $1,473.